PENGARUH TINGKAT PERPUTARAN MODAL KERJA DAN STRUKTUR MODAL TERHADAP PROFITABILITAS - Stifvani, Amelia; Rahayu, Yuliastuti (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The research is conducted in order to examine the influence of cash turnover (CT), inventory turnover(IT), current ratio (CR) and debt ratio to equity ratio (DER) to profitability (ROI) on cosmetics and householdneeds companies which are listed in the Indonesia Stock Exchange (IDX) in 2009-2015 periods. The independentvariablesare cash turnover, inventory turnover, current ratio and debt to equity ratio.The dependent variable inthis research is profitability. The samples are cosmetics and household needscompanieswhich are listed inIndonesia Stock Exchange (IDX) in 2009-2015 periods. The sample collection method has been done by usingpurposive sampling and 5 companies have been selected as sample. The analytical method has been done by usingmultiple regression analysis. The result of the test shows that cash turnover has significant influence to theprofitability because cash turnover has significance level 0.000 or less than alpha 0.05. Meanwhile, inventoryturnover, current ratio, debt to equity ratio do not haveany significant influenceto the profitability because thesignificance level of inventory turnover is 0.276,current ratio 0.729, debt ratio to equity 0.895 or largerthanalpha 0.05.Keywords: Return on investment, cash turnover, inventory turnover, current ratio, debt to equity ratio.